2023
DOI: 10.1002/cbic.202200566
|View full text |Cite
|
Sign up to set email alerts
|

Design of Artificial Enzymes: Insights into Protein Scaffolds

Abstract: The design of artificial enzymes has emerged as a promising tool for the generation of potent biocatalysts able to promote new-to-nature reactions with improved catalytic performances, providing a powerful platform for wide-ranging applications and a better understanding of protein functions and structures. The selection of an appropriate protein scaffold plays a key role in the design process. This review aims to give a general overview of the most common protein scaffolds that can be exploited for the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 215 publications
(422 reference statements)
0
9
0
Order By: Relevance
“…The phenomenon of the changed activity of the metal catalyst as a result of interaction with a protein remains in agreement with the literature reports regarding artificial metalloenzymes. 30,39–41…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon of the changed activity of the metal catalyst as a result of interaction with a protein remains in agreement with the literature reports regarding artificial metalloenzymes. 30,39–41…”
Section: Resultsmentioning
confidence: 99%
“…The phenomenon of the changed activity of the metal catalyst as a result of interaction with a protein remains in agreement with the literature reports regarding artificial metalloenzymes. 30,[39][40][41] To gain a deeper understanding of the studied process, the reaction time course was recorded (Fig. 2) under optimised conditions (Table 2, entry 11).…”
Section: Chemoenzymatic Cascade Optimisationmentioning
confidence: 99%
“…In the RCM reaction of N-tosyldiallylamine (TDA, 16), a benchmark reaction for evaluating the OM reaction activities of various catalysts, both 11 -S and 11 -O exhibited product yields greater than 90%, similar to HG-II (1) (entries 1-6). The complexes also mediated the RCM of the diallyl malonate ester (17) (entries 7-9) and the CM between compounds 18 and 19 (entries [10][11][12]. Regarding the reaction rate (Fig.…”
Section: Om Activities Of Ruthenium Complexesmentioning
confidence: 95%
“…In fact, various functional groups were attached to the NHC and/or benzylidene ligands to develop recyclable metathesis catalysts, [5][6][7] solid-phase metathesis reaction systems, 8,9 and biocatalysts hybridized with proteins. 3,[10][11][12][13] In particular, modifying the alkoxybenzylidene ligand is a promising strategy for regulating the HG-type complex reactivity because the exchange between the ligand and an olefin substrate initiates an OM catalytic cycle. Accordingly, some studies have demonstrated the electronic control of the phenyl ring by introducing a substituent group, 14,15 while others have reported the replacement of the alkoxy part in the benzylidene ligand with an imide-, 16,17 sulfone, 18 sulfonamide, 18 or formyl group.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial metalloenzymes (ArMs) represent an avenue to new-to-nature reactions. 1–4 These systems expand the biocatalytic toolbox by using transition metal complexes tethered to protein scaffolds; notable examples of chemical transformations using ArMs include transfer hydrogenation, 5 hydroformylation, 6,7 in vivo metathesis, 8 lignin oxidation, 9 Friedel–Crafts alkylation 10 and other cross-coupling reactions. 11…”
Section: Introductionmentioning
confidence: 99%